BOND STRENGTH DURABILITY of SELF-ETCHING ADHESIVES and RESIN CEMENTS TO DENTIN - Lima Chaves, Carolina de Andrade [UNESP] (2009)
Objectives: To evaluate the microtensile bond strength (mu TBS) of one-(Xeno III, Dentsply) and two-step (Tyrian-One Step Plus, Bisco) self-etching adhesive systems bonded to dentin and cemented to chemically cured (C&B Metabond) or light-cured paste of a dual-cure resin cement (Variolink II, Ivoclar) within a short (24 h) and long period of evaluation (90 days). Material and Methods: Forty recently extracted human molars had their roots removed and their occlusal dentin exposed and ground wet with 600-grit SiC paper. After application of one of the adhesives, the resin cement was applied to the bonded surface and a composite resin block was incrementally built up to a height of 5 mm (n = 10). The restored teeth were stored in distilled water at 37 C for 7 days. The teeth were then cut along two axes (x and y), producing beam-shaped specimens with 0.8 mm(2) cross-sectional area, which were subjected to mu TBS testing at a crosshead speed of 0.05 mm/min and stressed to failure after 24 h or 90 days of storage in water. The mu TBS data in MPa were subjected to three-way analysis of variance and Tukey's test (alpha = 0.05). Results: The interaction effect for all three factors was statistically significant (three-way ANOVA, p < 0.001). All eight experimental means (MPa) were compared by the Tukey's test (p < 0.05) and the following results were obtained: Tyrian-One Step Plus /C&B/24 h (22.4 +/- 7.3); Tyrian-One Step Plus /Variolink II/24 h (39.4 +/- 11.6); Xeno III/C&B/24 h (40.3 +/- 12.9); Xeno III/Variolink II/24 h (25.8 +/- 10.5); Tyrian-One Step Plus / C&B/90 d (22.1 +/- 12.8) Tyrian-One Step Plus/VariolinkII/90 d (24.2 +/- 14.2); Xeno III/C&B/90 d (27.0 +/- 13.5); Xeno III/Variolink II/90 d (33.0 +/- 8.9). Conclusions: Xeno III/Variolink II was the luting agent/adhesive combination that provided the most promising bond strength after 90 days of storage in water.